The effect of fiber-rich milk and equi-carbohydrate snack on glycemic and insulin response and satiety feeling (Medical Journal of Indonesia, 2016)
Background: Additional dietary fibers which can decrease the glycemic response by slowing down digestion whilst maintaining the available carbohydrate content is one approach of healthy diet. This study aimed to compare post-prandial glycemic and insulin response, hunger and satiety feeling after consuming fiber-rich milk compare with equi-carbohydrate food as morning snack in healthy adults. Methods: Cross-over study was conducted on 12 healthy subjects who fulfilled the criteria. Each test food was given after consuming standard breakfast. Venous blood samples for insulin and glucose level were taken before consuming test food, at 30, 60, 120, and 180 minutes after, and plotted against time to generate a curve. Hunger and satiety assessments were taken by visual analog scale (VAS) after each blood sampling. Results: In average, age was 30.8+4.3 years old, body mass index was 20.6±1.6 kg/m2. Seven of twelve subjects were females. There were significantly differences in postprandial glycemic response (p<0.001), insulin response (p=0.045) and hunger feeling (p=0.021) between the two foods. However, postprandial satiety feelings were not different significantly (p=0.357). The glycemic response area under the curve of fiber-rich milk was significantly lower than the equi-carbohydrate snack (p=0.010). Conclusion: Differences in glycemic and insulin response, and hunger feeling between two test foods, suggesting that fiber-rich milk can be used as an alternative snack for healthy adults. Further study is needed for the use of fiber-rich milk as an alternative snack for pre-diabetic patients.